2023
DOI: 10.1371/journal.pone.0281676
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium-enhanced MRI visualizing backflow at increasing intra-renal pressure in a porcine model

Abstract: Introduction Intrarenal backflow (IRB) is known to occur at increased intrarenal pressure (IRP). Irrigation during ureteroscopy increases IRP. Complications such as sepsis is more frequent after prolonged high-pressure ureteroscopy. We evaluated a new method to document and visualize intrarenal backflow as a function of IRP and time in a pig model. Methods Studies were performed on five female pigs. A ureteral catheter was placed in the renal pelvis and connected to a Gadolinium/ saline solution 3 ml/L for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…[ 11 ], showing that damage due to experimental vesicoureteral reflux in some of the less severely affected areas of the kidney, appeared to be limited to the center of the medullary pyramid with normal renal parenchyma at the borders. Additionally, it appears that IRB happens first and at lower pressures in the upper pole [ 13 ], which is consistent with compound papillae being more frequently observed in the upper calyces in both human and pig kidneys [ 11 ].…”
mentioning
confidence: 66%
See 4 more Smart Citations
“…[ 11 ], showing that damage due to experimental vesicoureteral reflux in some of the less severely affected areas of the kidney, appeared to be limited to the center of the medullary pyramid with normal renal parenchyma at the borders. Additionally, it appears that IRB happens first and at lower pressures in the upper pole [ 13 ], which is consistent with compound papillae being more frequently observed in the upper calyces in both human and pig kidneys [ 11 ].…”
mentioning
confidence: 66%
“…Based on animal studies and studies during retrograde pyelography in humans, pyelotubular backflow occurs at 20–30 mmHg (27–41 cmH 2 O), pyelovenous backflow at 30–50 mmHg (41–68 cmH 2 O), and forniceal rupture at 70–200 mmHg (95–272 cmH 2 O) [ 1 , 2 ]. Newer studies using dynamic gadolinium-enhanced MRI have suggested, however, that IRB may occur at considerably lower pressures, starting at mean pressures as low as 15 mmHg (20 cmH 2 O) [ 13 ]. Thus, it seems logic that IRB happens as a continuous function of pressure, initially appearing in the center of the medullary pyramid, where the collecting ducts are less protected against reflux, compared to the peripheral ducts that end on the oblique part of the papillary surface.…”
mentioning
confidence: 99%
See 3 more Smart Citations